(untitled) (American Journal of Applied Statistics and Economics, 2023)
Foreign direct investment (FDI) has grown significantly in developing countries over recent decades, and governments in these countries now regard FDI as a key component of their development strategy. The potential benefits of FDI include the provision of financial resources, job creation, increased economic growth and spillover effects on local businesses. In addition, the development effectiveness of FDI depends on the ability of host countries to absorb technology and innovation from foreign companies. Technology transfer (TT) is therefore a major issue in the context of FDI. Political institutions and economic players need to work together to encourage effective and sustainable technology transfer. Technology transfer is therefore an essential process in enabling companies to remain competitive and innovate in a constantly changing economic environment. Technology transfer centers play a crucial role in this process, facilitating the exchange of knowledge and technology between the various players in the innovation ecosystem. After examining the two variables, Foreign Direct Investment (FDI) and TT on economic growth, the results indicate that both variables have a positive impact on economic growth